Pengaruh Terapi Perilaku Kognitif Terhadap Tingkat State Anxiety Pada Mahasiswa Keperawatan Selama Menjalani Praktik Klinik - Suci Ramadhani; Donsu, Jenita Doli Tine; Laasara, Nurun (Caring : Jurnal Keperawatan, 2023)
State anxiety in nursing students occurs of being triggered by stress during clinical practice. The problems decreasing student performance. Therefore, an intervention is needed to create an adaptive coping strategy, one alternative is using Cognitive Behavioral Therapy. The aim of this study is to determine the effect of Cognitive Behavioral Therapy on the level of state anxiety. The type of this study uses a quasi-experimental research with purposive sampling thechnique. The study was conducted on April 18-26, April 2022. The research respondent were student of the 4th term on Anesthesiology Nursing students who are undergoing clinical practice. Total population consist of 95 respondents with the sample used is 54 respondents. P-value show 0.000, it means there is a significant influence on the Cognitive Behavioral Therapy intervention on the level of state anxiety. State anxiety that occurs in nursing student during clinical practice can be overcome by using Cognitive Behavioral Therapy intervention.   State anxiety mahasiswa keperawatan muncul akibat adanya peningkatan stres selama menjalani praktik klinik. Problematika yang terjadi menurunkan kinerja mahasiswa. Oleh karena itu, dibutuhkan intervensi yang ditujukan untuk menciptakan strategi koping yang adaptif, salah satu alternatifnya dengan menggunakan Terapi Perilaku Kognitif. Diketahuinya pengaruh Terapi Perilaku Kognitif terhadap tingkat state anxiety. Jenis penelitian yang digunakan adalah kuasi eksperimental dengan teknik purposive sampling. Penelitian dilakukan pada 18-26 April 2022. Responden penelitian yaitu mahasiswa Keperawatan Anestesiologi semester 4 yang sedang menjalani praktik klinik. Total populasi terdiri dari 95 responden dengan sampel yang digunakan adalah sebanyak 54 responden. Nilai p-value menunjukkan 0.000, artinya terdapat pengaruh Terapi Perilaku Kognitif terhadap tingkat state anxiety. State anxiety yang terjadi pada mahasiswa keperawatan selama menjalani praktik klinik dapat diatasi dengan menggunakan intervensi Terapi Perilaku Kognitif.